Population Dynamics of Hymenia Recurvalis (FAB.) (Amaranth Leaf Webber) in Garhwal Hills of Uttrakhand - Aswal, J. S.; Bisht, B. S. (Indian Journal of Hill Farming, 2018)
In the present study, an attempt has been made to understand the population dynamics of the Hymenis recurvalis in different elevations of Garhwal hills. Light traps were installed at three different experimental sites viz. Khadi, (950 m asl) at tropical, Gaza (1450 m asl) at sub-tropical and Ranichauri (1750 m asl) in the temperate region. The pest appearance was from 27th standard week (first week of July) (1.42-3.90moth/night) up to 46th standard week (26th November to 2nd December) (1.60-2.0moth/night). first appearance of adult moths (3.90) were recorded at Khadi (tropical), and Gaza (sub-tropical) (1.42) during 27th standard week (first week of July) and thereafter, it appeared at Ranichauri (Temperate) (2.0) during the 28th standard week (second week of July). It is clear that the moths first appeared at lower elevations then spread towards higher elevations. The number of catches with highest peak were observed at 24.66 moths/night at Khadi, 30.0 moths/night at Gaza and 17.14 moths/night at Ranichauri during 39th the week (September last week) respectively, which gradually declined after 40th week and sharply declined from 44th week.